Development Of Linkage Mechanism For In-Pipe Robot - Lim, Wen Kai (Universiti Sains Malaysia, 2022)
Humans have carried out pipeline inspection work to watch for and find any leaks, particularly in industrial facilities, chemical plants, natural gas pipelines, and oil rigs. This workplace is the most hazardous and has a high likelihood of endangering employees in the short or long term. In order to solve this issue, in-pipe inspection robots have been developed to take the position of workers and have improved performance over manual inspection. The goal of this project is to create an in-pipe robot capable of turning in a steady manner at pipe junctions of varying diameters found in commerce and industry. Robot design, including turning mechanism for pipe corner and surrounding area. The purpose of this project is to design an in-pipe robot which is capable to move in the pipe and turning in stable condition without wear and tear problem in the pipe junction with various diameter in the market and industry. The robot's design includes a mechanism for turning around a pipe corner and a point of contact to keep the robot stable as it travels through the pipeline. Using Arduino UNO as the robot's "brain" to transfer electrical supply to its locomotion, a control system is constructed in the robot's body to rotate the wheels and make it mobile in the pipeline.